Aliphatic and chlorinated alkenes and epoxides as inducers of alkene monooxygenase and epoxidase activities in Xanthobacter strain Py2. - Ensign, S A (1996)
The inducible nature of the alkene oxidation system of Xanthobacter strain Py2 has been investigated. Cultures grown with glucose as the carbon source did not contain detectable levels of alkene monooxygenase or epoxidase, two key enzymes of alkene and epoxide metabolism. Upon addition of propylene to glucose-grown cultures, alkene monooxygenase and epoxidase activities increased and after an 11-h induction period reached levels of specific activity comparable to those in propylene-grown cells. Addition of chloramphenicol or rifampin prevented the increase in the enzyme activities. Comparison of the banding patterns of proteins present in cell extracts revealed that polypeptides with molecular masses of 43, 53, and 57 kDa accumulate in propylene-grown but not glucose-grown cells. Pulse-labeling of glucose-grown cells with [35S]methionine and [35S]cysteine revealed that the 43-, 53-, and 57-kDa proteins, as well as two additional polypeptides with molecular masses of 12 and 21 kDa, were newly synthesized upon exposure of cells to propylene or propylene oxide. The addition to glucose-grown cells of a variety of other aliphatic and chlorinated alkenes and epoxides, including ethylene, vinyl chloride (1-chloroethylene), cis- and trans-1,2-dichloroethylene, 1-chloropropylene, 1,3-dichloropropylene, 1-butylene, trans-2-butylene, isobutylene, ethylene oxide, epichlorohydrin (3-chloro-1,2-epoxypropane), 1,2-epoxybutane, cis- and trans-2,3-epoxybutane, and isobutylene oxide stimulated the synthesis of the five propylene-inducible polypeptides as well as increases in alkene monooxygenase and epoxidase activities. In contrast, acetylene, and a range of aliphatic and chlorinated alkanes, did not stimulate the synthesis of the propylene-inducible polypeptides or the increase in alkene monooxygenase and epoxidase activities.